Assessing the appropriateness of blood transfusion among injured patients at a Ghanaian tertiary hospital: Time for clarity on the use of a scarce resource. Issue 5 (May 2021) - Gyedu, Adam; Goodman, Stephanie K; Quansah, Robert; Osei-Ampofo, Maxwell; Donkor, Peter; Mock, Charles
Highlights: 20% – 33% of injured patients presenting to a Ghanaian tertiary hospital who needed blood transfusion did not receive one 30% – 39% of injured patients presenting to a Ghanaian tertiary hospital who did not need blood transfusion received one Blood transfusion practice was inappropriate in 31% – 39% of all injured patients presenting to a Ghanaian tertiary hospital Assessing the appropriateness of blood transfusion among injured patients at a Ghanaian tertiary hospital: Time for clarity on the use of a scarce resource Abstract: Introduction: Hemorrhage is an important cause of preventable injury-related death. Many low- and middle-income country (LMIC) patients do not have timely access to safe blood. We sought to determine the degree of appropriateness of blood transfusion among patients with injuries requiring surgical intervention at presentation to a tertiary hospital in Ghana. Methods: We performed a retrospective review of such patients presenting to Komfo Anokye Teaching Hospital (KATH), from January 2015 to December 2016. Patients' hemoglobin levels at presentation were determined as the first record of hemoglobin after presentation and their receipt of blood transfusion was determined by explicit documentation in the chart. We defined appropriate blood transfusion practice as patients receiving transfusion when hemoglobin was equal or below a threshold, or patients not being transfused when hemoglobin was above the threshold. We considered both restrictive (hemoglobin ≤7 g/dL) and liberal (hemoglobin ≤10 g/dL) transfusion thresholds. Results: There were 1, 408 patients who presented to KATH with injuries that met inclusion criteria. Two hundred and ninety two (292) patients were excluded because of missing hemoglobin information. Four hundred and fifty eight (458;41%) patients received blood transfusion. Transfused patients had a higher mean age (38 vs 35 years) and were less likely to be male (62% vs 71%). Transfused patients underwent more external fixation procedures (28% vs 19%), trauma amputations (5% vs 1%) and trauma laparotomies (3% vs 1%). At a restrictive transfusion threshold (hemoglobin ≤7 g/dL), 20% of patients who needed a transfusion did not receive one and 39% of patients who did not need a transfusion received one. At a liberal threshold (hemoglobin ≤10 g/dL), 33% of patients who needed a transfusion did not receive one and 30% of patients who did not need a transfusion received one. Blood transfusion practice was inappropriate in 31%–39% of all patients. Conclusion: Our data suggest that clearer guidelines for blood transfusion among emergency surgery patients are needed in Ghana and similar LMICs to avoid inappropriate use of blood as a scarce resource.